The presence of mealybugs (Hemiptera : Pseudococcidae) on Chrysanthemum morifolium ramat - Yuliani Nur Aisyah,; Dewi Sartiami, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Chrysanthemum morifolium is the most exported ornamental cut flower in Indonesia. Its cultivation cannot be separated from pests attacks, especially mealybugs which affect its sale value. This study aimed to identify mealybugs species on C. morifolium, to determine population density, the intensity attack level and damage symptom of Phenacoccus solenopsis. Mealybug identification was carried out by collecting mealybugs and preparing the slides mount. The population density and attack intensity of Ph. solenopsis were observed on three varieties of chrysanthemum. The damage symptom caused by mealybugs, a certain number of Ph. solenopsis were infested to the plants and observed. The result shows that there are four mealybugs species, i.e Ferrisia virgata, Ph. solenopsis, Planacoccus minor, and Pseudococcus jackbeardsleyi. From this study, F. virgata and Pl. minor are newly recorded mealybugs pests found on chrysanthemum. The highest population of Ph. solenopsis is recorded in White Reagent variety as many as 73.5 mealybugs per plot or 8.72% of intensity attack level. Malformation of vegetative phase of chrysanthemum reported as reduction of leaf size, wavy leaves, thickened, shriveled, curled, and twisted leaves. Further damage on generative phase caused up to 30 mealybug infestation showed the incurvation of bud and flower stalk, and reduction of overall plant size.